Alignment of Business Strategy and Information Technology in Special Economic Zone using Enterprise Architecture - Ahmad Ari Nugrahanto; Viany Utami Tjhin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In recent years, companies engaged in co-working space have provided services to entrepreneurs, startups, freelancers, developers, businesses, and their teams through information technology, increasing their massification and access. These are generally provided based on the government's objective to meet industry 4.0 requirements. Still, the differences in digitization and the lack of standard e-service complicate the balance in their business. On the other hand, enterprise architecture can be used for standardization, convergence, and interoperability in e-business. Moreover, it allows a holistic perspective to view the information technology resources of co-working space businesses and align them with their business strategy. This research aims to list some gaps between existing business architecture with enterprise architecture in co-working businesses in Batam, Indonesia Special Economic Zone.